The Influence of Droplet Size and Emulsifiers on the In Vitro Digestive Properties of Bimodal Oil-in-Water Emulsions - Takumi Umeda; Hiroyuki Kozu; Isao Kobayashi (Foods)
Lipids are often ingested via oil-in-water (O/W) emulsions, where interfacial properties and droplet size influence their digestibility. In this study, a bimodal O/W emulsion, termed Food Emulsion Blend (FEB), was prepared by mixing two monodisperse emulsions of different droplet sizes and compositions. The influence of droplet size and emulsifier type on in vitro digestion was evaluated. Soybean oil was used as the dispersed phase, and monodisperse emulsions were prepared via premix membrane emulsification using membranes with pore sizes of 1, 10, and 50 µm. Two selected emulsions were mixed in equal proportions to form FEB. The emulsifiers included 1.0% (w/w) Tween 20 (TW) or 0.5% (w/w) Tween 20 and 0.5% (w/w) citrus pectin (TWCP). The <semantics>d4,3</semantics> values of the emulsions stabilized by TW and TWCP ranged from 1.05 to 51.99 µm and from 1.19 to 46.94 µm, respectively. In vitro digestion revealed that all FEB samples retained bimodal size distributions post-gastric digestion. Free fatty acid release correlated strongly with the initial total droplet surface area for the TW- and TWCP-stabilized FEBs (R2 > 0.8). These results suggest that FEB allows for the precise control of lipid release, offering potential applications in food formulation.